Exploring Life Satisfaction as a Bridge Between Taqwa and Psychological Well-Being in Muslim Adolescents - Sufya, Dina Haya; Abas, Nurul Ain Hidayah (International Journal of Islamic Educational Psychology, 2024)
Life satisfaction is a crucial component of psychological well-being, and its role as a mediator between religious practices, such as taqwa, and overall mental health in Muslim adolescents is an emerging area of interest. The research aims to bridge the gap in understanding how religious values, particularly the love and fear of Allah, influence life satisfaction and psychological well-being. A mixed-methods approach with a convergent parallel design was employed to collect both quantitative and qualitative data. Quantitative data were gathered using validated scales. Qualitative data were obtained through open-ended questions to capture personal experiences. Structural Equation Modeling (SEM) was utilized to assess the direct and indirect relationships between variables, while qualitative analysis provided a contextual understanding of the quantitative findings. The quantitative analysis revealed that taqwa positively influenced both life satisfaction (path coefficient = 0.191, p < 0.001) and psychological well-being (path coefficient = 0.134, p = 0.005). Life satisfaction was found to significantly mediate the relationship between taqwa and psychological well-being, amplifying the beneficial effects of faith.  However, the fear of Allah was not directly associated with psychological well-being and may contribute to anxiety when not balanced with love for Allah. Qualitative responses emphasized that authentic spiritual engagement, such as the love and worship of Allah, fostered peace and happiness among students. The findings highlight the importance of nurturing love, hope, and gratitude toward Allah, suggesting that faith-based programs should emphasize these aspects to improve mental health. This research can inform the development of emotional resilience and spiritual fulfillment programs in Islamic boarding schools.